Overview of Factors Influencing Medication Adherence in Elderly Hypertension Patients - Aprianti, Pande Made Ayu; Marangyana, I Gede Bagus Indra; Sudiastini, Ni Ketut Ayu (Poltekkes Kemenkes Denpasar, 2025)
Hypertension is defined as a sustained increase in blood pressure with a systolic value of ≥140 mmHg and/or a diastolic value of ≥90 mmHg. The risk of developing hypertension increases progressively with age, with a prevalence of more than 60% among individuals over 60 years old (elderly). Treatment success for hypertension depends not only on accurate diagnosis and appropriate therapy but also on patients' adherence to antihypertensive medication. This study aimed to examine the relationship between factors such as knowledge about hypertension and family support with medication adherence among elderly hypertensive patients. Methods: This was an analytical observational study with a cross-sectional design conducted at Hospital X in Denpasar. A total of 70 elderly hypertensive patients participated in the study. Data were collected using the MMAS-8 (Morisky Medication Adherence Scale) to assess medication adherence, and validated questionnaires to measure knowledge of hypertension and family support. Data analysis was performed using the Spearman correlation test. Results: A significant relationship was found between knowledge about hypertension and medication adherence (p=0.000), with a Spearman correlation coefficient of r=0.657, indicating a strong correlation. A significant relationship was also found between family support and medication adherence (p=0.000), with a correlation coefficient of r=0.546, indicating a moderate correlation. Conclusion: Higher levels of knowledge about hypertension and stronger family support are significantly associated with better medication adherence among elderly hypertensive patients. Educational efforts and family involvement are recommended to improve adherence to antihypertensive therapy.